The “strength of the humbles”: memory and history of another Colombia in Vivan los compañeros (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
c publications, the “chocoano”  mo en la poesAlthough Carlos Arturo Truque (1927-1970) is still not well known, we cannot talk about Afro-Colombian, or Colombian literature, without mentioning his contribution. With an unfocused literary production in periodic publications, the “chocoano” bets on the short story when this genre was not highly valued in his country. Vivan los compañeros collects all his short stories (25), where he approaches the excluded characters of society as well as the more “shameful” episodes of Colombian history, from a language that distances itself from all academic art. His work, described at the time as “dirty literature” and specifically located in Chocó and the port of Buenaventura, is not alien to any human injustice. Besides, the need for Truque to express the speech of his community does not prevent him from contemplating new narrative techniques coming from North America. Thus, he renews the Colombian short story from the formal level and its content.
Keywords: Afro-colombian literature; contemporary tale; La Violencia Literature; memory and history; language and identity.